Features of model thin-film solar cells photoelectric characteristics based on a non-toxic multi-component connection CuZn₂AlS₄ - Sergeyev, D; Shunkeyev, K.; Kuatov, B.; Zhanturina, N. (Eurasian Journal of Physics and Functional Materials, 2026)
In this paper, the features of the characteristics of model thin-film solar cells based on the non-toxic multicomponent compound CuZn2AlS4(CZAS) are considered. The main parameters (open-circuit voltage, short-circuit current, fill factor, efficiency) and characteristics (quantum efficiency, current-voltage characteristic) of thin-film solar cells based on CZAS have been determined. The minimum optimal thickness of the CZAS absorber is found (1-1.25 microns). Deterioration of the performance of solar cells with an increase in operating temperature (280-400 K) is shown. It is revealed that in the wavelength range of 390-500 nm CZAS has a high external quantum efficiency, which allows its use in designs of multi-junction solar cells designed to absorb solar radiation in the specified range. It is shown that the combination of CZAS films with a buffer layer of non-toxic ZnS increases the performance of solar cells.Recommended CitationSergeyev, D.; Shunkeyev, K.; Kuatov, B.; and Zhanturina, N. (2021) "Features of model thin-film solar cells photoelectric characteristics based on a non-toxic multi-component connection CuZn₂AlS₄," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 3, Article 9.DOI: https://doi.org/10.32523/ejpfm.2021050309